2017
DOI: 10.1186/s12913-017-2457-z
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of an electronic clinical decision support system for improving quality of antenatal and childbirth care in rural Tanzania: an intervention study

Abstract: BackgroundQUALMAT project aimed at improving quality of maternal and newborn care in selected health care facilities in three African countries. An electronic clinical decision support system was implemented to support providers comply with established standards in antenatal and childbirth care. Given that health care resources are limited and interventions differ in their potential impact on health and costs (efficiency), this study aimed at assessing cost-effectiveness of the system in Tanzania.MethodsThis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…This result does not confirm the hypothesis that the use of an eCDSS would increase the number of essential ANC interventions. However, this unexpected result is consistent with previous studies conducted on the effects of an eCDSS in Ghana and South Africa, which demonstrated that although the performance of healthcare workers improved somewhat, no significant improvement in the overall quality score of ANC was found after implementation of the eCDSS (Horner et al, 2013;Mensah et al, 2015;Saronga et al, 2017). Our results may indicate that at intervention facilities where the NAA was used, essential components of ANC service delivery were skipped more than in control facilities.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result does not confirm the hypothesis that the use of an eCDSS would increase the number of essential ANC interventions. However, this unexpected result is consistent with previous studies conducted on the effects of an eCDSS in Ghana and South Africa, which demonstrated that although the performance of healthcare workers improved somewhat, no significant improvement in the overall quality score of ANC was found after implementation of the eCDSS (Horner et al, 2013;Mensah et al, 2015;Saronga et al, 2017). Our results may indicate that at intervention facilities where the NAA was used, essential components of ANC service delivery were skipped more than in control facilities.…”
Section: Discussionsupporting
confidence: 91%
“…Respondents mentioned that they believed an eCDSS would especially improve record-keeping, performance of healthcare workers, and communication between healthcare workers and pregnant women (Van Pelt et al, 2020;. However, a program implementing an eCDSS in three sub-Saharan African countries found no significant improvement in the overall quality of the delivery of ANC (Mensah et al, 2015;Saronga et al, 2017). Evaluating the impact of an eCDSS on daily work practices and quality of care is essential when considering sustained use of a digital health tool among healthcare workers.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in other medical areas such as the gynecological care in rural areas with supposedly poor medical infrastructure in Tanzania or Ghana, an improvement of the processes (by CDSS support) did not yet lead a higher cost efficiency [56, 57]. In summary, the current study situation is heterogeneous, and CDSS may not always be clearly cost effective.…”
Section: Improving Cost Efficiencymentioning
confidence: 82%
“…Considering only additional costs implementing computer-assisted CDSSs, the cost per pregnancy complication detected was US $285 [ 20 ]. In Tanzania, ICERs were 2013 US $2469 and US $338 per 1% change in process quality for antenatal and childbirth care, respectively [ 4 ].…”
Section: Discussionmentioning
confidence: 99%